EFL Instruction in Ict-Cultured Environment : Teachers’ Challenges and Roles - HAMAMAH, M.Pd. (Jurnal Humanitas)
The advances in technology surrounding EFL instructions have served to expand learning experiences beyond the traditional classroom. It is stimulating to help the students achieving the goal of acquiring the target language. However, some teachers have anxiety in dealing with this due to their unfamiliarity to the technology. This article discusses EFL teachers’ challenges in facing ICT-cultured environment and the ways of redefining teachers’ role in order to make the students learn efficiently, autonomously, and responsibly in process of language learning, in Indonesian context. With the enormous chance to access information in the presence of ICT, it is expected that students can be nurtured to build up independence in the EFL learning.